Diffusion-based non-uniform regularization for variational shape deformation. (December 2016) - Zhu, Lifeng; Li, Wei; Zhang, Xiaorui; Song, Aiguo
Abstract: Regularization is a typical technique to correct the discontinuity artifacts at the control points in shape deformation. A regularizer with higher weights is required if the deformation is large, which will unfortunately distort the entire shape. In this work, we present a non-uniform regularization technique based on a shape-aware scalar field obtained from diffusion, which allows user to control the magnitude and range of the regularizer around specific control points. Experimental results show that shapes are deformed smoothly and no over-regularized artifact is observed with our non-uniform regularizer. Highlights: Nonuniform regularization with good trade-off between shape smoothness and distortion. A diffusion-based model for nonuniform regularization and its efficient approximation. Flexible control to adjust the amount of the regularization around each control point.